2020
DOI: 10.3329/bjo.v23i1.45108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anterior Nasal Packing on Eustachian Tube Function and Middle Ear Pressure

Abstract: The present study includes evaluation 60 ears of 30 nasal patients admitted to department of Otolaryngology and Head-Neck Surgery at Banghabandhu Sheikh Mujib Medical University. Each patient underwent nasal surgery followed by anterior nasal packing for 48 hours. All patients were investigated by tympanometry prior to surgery, 2nd post operative day before pack removal and on 7th post operative day 5 days after pack removal. This study shows that nasal packing result in Eustachian tube dysfunction and negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(2 reference statements)
1
1
0
Order By: Relevance
“…To find out any statistically significant difference between preoperative mean middle ear pressure and mean middle ear pressure after 24 hours of ANS pack, t-test was done and it was found significant (p <0.001). This result is similar to another study which showed 43.33% of ears had abnormal middle ear pressure 9 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…To find out any statistically significant difference between preoperative mean middle ear pressure and mean middle ear pressure after 24 hours of ANS pack, t-test was done and it was found significant (p <0.001). This result is similar to another study which showed 43.33% of ears had abnormal middle ear pressure 9 .…”
Section: Resultssupporting
confidence: 92%
“…The mean prior operation middle ear pressure was -24 daPa 8 . Middle ear pressure range between "-50 daPa to 0 daPa" were maximum (53.33%) preoperatively in another Bangladeshi study 9 .…”
Section: Resultsmentioning
confidence: 84%